Reduced-risk insecticides can effectively manage thrips without compromising Orius predation in pepper production - Arnol Ariel Gomez-Santos; Ashley Leach (Biological Control, 2025)
The western flower thrips (WFT), Frankliniella occidentalis (Pergande) is a key pest in fruiting vegetables worldwide, causing significant yield losses in peppers via feeding on leaves, flowers and fruits. While pepper growers rely heavily on insecticides for WFT management, some insecticide products may compromise natural enemies, like minute pirate bugs (Orius spp., Hemiptera: Anthocoridae), crucial predators of thrips. To assess the performance of insecticides in bell pepper production, we conducted field trials and laboratory bioassays. Field trials were conducted to assess the impact of six insecticides (isocycloseram, cyantraniliprole, spinetoram, spirotetramat, λ-cyhalothrin and imidacloprid) on densities of WFT and Orius and yield. In a follow-up bioassay, we exposed minute pirate bugs (Orius insidiosus (Say)), to insecticide residues and measured their mortality and predation of WFT. Results indicate that broad-spectrum insecticides significantly reduced field Orius populations by up to 80 %, while reduced-risk insecticides like cyantraniliprole and spirotetramat had minimal impact. Furthermore, while insecticide management contributed to WFT suppression, its impact on yield was minimal, indicating that factors beyond WFT management may play a more significant role in determining productivity in pepper production systems. Laboratory insecticide residual bioassays further demonstrated that exposure to broad-spectrum insecticide residues significantly increased mortality of O. insidiosus and decreased predation of WFT. In contrast, the residues of selective insecticides did not significantly impact mortality and overall predation of WFT. These findings support the use of cyantraniliprole, spirotetramat and spinetoram as effective insecticides in sustainable pest management programs that effectively reduce WFT while preserving Orius populations and their predatory function.